2019
DOI: 10.1136/bmjophth-2019-000322
|View full text |Cite|
|
Sign up to set email alerts
|

Implantation of Scharioth macula lens in patients with age-related macular degeneration: results of a prospective European multicentre clinical trial

Abstract: ObjectiveTo report the visual and refractive outcomes following monocular implantation of a supplementary (piggyback) Scharioth macula lens (SML) in previously pseudophakic eyes with age-related macular degeneration (AMD).Methods and analysisProspective European multicentre clinical trial. 50 eyes of 50 pseudophakic patients with either dry or previously treated and stable neovascular AMD for at least 6 months were included. The inclusion criteria were age over 55, corrected distance visual acuity (CDVA) of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Intraocular pressure remained practically unchanged in these studies. 11,15,24 Not even a transient increase in IOP was observed in this study; however, such changes have been reported in connection with the Sulcoflex Trifocal 703F supplementary IOL (Rayner Intraocular Lenses Ltd; Worthing, UK). 25 The convexconcave geometry, along with the four flexible loop haptics ensure enough space in the sulcus.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Intraocular pressure remained practically unchanged in these studies. 11,15,24 Not even a transient increase in IOP was observed in this study; however, such changes have been reported in connection with the Sulcoflex Trifocal 703F supplementary IOL (Rayner Intraocular Lenses Ltd; Worthing, UK). 25 The convexconcave geometry, along with the four flexible loop haptics ensure enough space in the sulcus.…”
Section: Discussionmentioning
confidence: 44%
“…No complications were observed during surgery or in the postoperative period, which is a finding similar to previous studies involving the same ciliary sulcus lens family. 10,11,14,15,24 The design of the tested lenses supports the integrity and physiologic function of the anterior segment of the eye. Intraocular pressure remained practically unchanged in these studies.…”
Section: Discussionmentioning
confidence: 86%
“…There (41) and provided more information about the visual and refractive outcomes. Although the SML does not offer distance magnification, it can magnify 2× for objects in a range of 10-15 cm from the eye and can be implanted through a 2.2 mm incision with a reduction of postoperative astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…There were 3 articles included in this review about SML, with 91 patients participated for follow-up from 3 to 12 months (41)(42)(43). In 2019, a prospective multicenter clinical trial done by Srinivasan reported the visual outcomes following monocular SML implantation in pseudophakia eyes with AMD (41). It includes 50 patients and a follow-up for 12 months.…”
Section: Scharioth Macular Lens (Sml)mentioning
confidence: 99%
“…The interesting development about EyeMax Mono was to provide a high-quality image in all areas of the macular extending up to 10° from the fovea in case of preferred retina location changes or AMD progression (19). Recently, a prospective multicenter clinical trial about the Scharioth macula lens (SML) in previous pseudophakic eyes with AMD was published (20). Although the SML does not offer distance magnification, it can magnify 2× for objects in a range of 10-15 cm from the eye and can be implanted through 2.2 mm incision with a reduction of postoperative astigmatism.…”
mentioning
confidence: 99%